Investigating and improving cardiac troponin assays - Salonen, Selma (fi=Turun yliopisto|en=University of Turku|, 2025)
Cardiac troponins I (cTnI) and T (cTnT) are the preferred biomarkers of myocardial injury representing the diagnostic cornerstone of acute myocardial infarction (AMI). The implementation of high-sensitivity cardiac troponin (hs-cTn) assays has provided faster and more accurate detection of myocardial injury but also reduced clinical specificity for AMI. Current hs-cTnT assays targeting intact as well as degraded cTnT forms (i.e. total cTnT) can often detect hs-cTnT elevations in several other conditions, such as chronic kidney disease (CKD). Recently, intact and mildly degraded cTnT forms (i.e. long cTnT) have shown promise as a more specific biomarker for AMI. However, their detection requires particularly high analytical sensitivity. In addition to the specificity issues, hs-cTn assays are also prone to interferences caused by cardiac troponin-specific autoantibodies (cTnAAbs), which can lead to either false-positive or false-negative hs-cTn results. The aim of this thesis was to develop a highly sensitive immunoassay for long forms of cTnT using upconversion luminescence (UCL). The analytical and diagnostic performance of the developed assay was evaluated, and long cTnT concentrations were measured in patients with advanced CKD not on dialysis to assess associations between long cTnT and adverse long-term outcomes. In addition, the effect of cTnAAbs on the elimination of cTn measured by five widely used commercial hs-cTn assays was investigated. A highly sensitive UCL-based long cTnT assay with a limit of detection of 0.4 ng/L was successfully developed. The assay showed excellent discrimination between patients with non-ST elevation myocardial infarction and end-stage renal disease. Furthermore, long cTnT was independently associated with all-cause mortality in patients with CKD stage 4–5. The novel long cTnT assay can serve as a valuable tool for discovering the full potential of long cTnT as a biomarker for AMI. For the first time, cTnAAbs and the formation of large macrotroponin complexes were also shown to lead to reduced cTn clearance, which has been previously speculated to be the underlying mechanism of positive cTnAAb-mediated interference. Increased understanding of cTnAAb-related interferences is important both in clinical practice and in the development of new generations of hs-cTn assays.

Sydänperäisiä troponiineja tunnistavien määritysten tutkiminen ja kehittäminen Sydänperäiset troponiinit I (engl. cardiac troponin I, cTnI) ja T (engl. cardiac troponin T, cTnT) ovat sydänlihasvaurion biomerkkiaineita ja tärkeä osa sydän-infarktidiagnostiikkaa. Herkät troponiinitestit ovat mahdollistaneet sydänlihasvaurion varhaisen ja tarkan tunnistamisen, mutta samalla spesifisyys sydäninfarktille on laskenut. Nykyiset cTnT-testit havaitsevat sekä kokonaisen että pilkkoutuneen cTnT:n (totaali cTnT) ja mittaavat kohonneita pitoisuuksia usein myös muiden sairauksien, kuten munuaisten vajaatoiminnan yhteydessä. Kokonaiset ja vähän pilkkoutuneet cTnT-muodot (pitkä cTnT) ovat osoittautuneet hiljattain lupaaviksi sydäninfarktin merkkiaineiksi, mutta niiden havaitseminen vaatii erittäin herkkää määritysmenetelmää. Spesifisyysongelmien lisäksi herkät troponiinitestit ovat alttiita troponiiniautovasta-aineiden aiheuttamille häiriöille, jotka voivat johtaa joko vääriin positiivisiin tai vääriin negatiivisiin testituloksiin. Väitöstutkimuksen tavoitteena oli kehittää erittäin herkkä immunomääritys pitkille cTnT:n muodoille hyödyntäen käänteisviritteistä luminesenssia. Kehitetyn määrityksen analyyttistä ja diagnostista suorituskykyä arvioitiin, ja pitkän cTnT:n yhteyttä pitkän aikavälin haitallisiin lopputuloksiin tutkittiin vaiheen 4–5 munuaistautia sairastavilla potilailla ennen dialyysihoidon aloitusta. Lisäksi troponiiniautovasta-aineiden vaikutusta troponiinien puhdistumiseen verenkierrosta tutkittiin viidellä eri kaupallisella testillä. Kehitetty käänteisviritteiseen luminesenssiin perustuva pitkän cTnT:n määritys saavutti 0,4 ng/L:n havaitsemisrajan ja kykeni erinomaisesti erottelemaan sydäninfarktipotilaat ilman ST-nousua loppuvaiheen munuaistautia sairastavista potilaista. Lisäksi pitkän cTnT:n havaittiin olevan itsenäisesti yhteydessä kuolleisuuteen predialyysipotilailla. Tulevaisuudessa määritys on tärkeä työkalu tutkittaessa pitkän cTnT:n potentiaalia sydäninfarktin merkkiaineena. Tutkimuksessa todistettiin myös ensimmäistä kertaa troponiiniautovasta-aineiden muodostamien makrotroponiini-kompleksien johtavan troponiinien pienentyneeseen puhdistumiseen verenkierrosta aiheuttaen siten kohonneita troponiinipitoisuuksia. Autovasta-aineiden aiheuttamien häiriöiden parempi ymmärrys on olennaista sekä kliinisessä käytännössä että kehitettäessä uuden sukupolven troponiinimäärityksiä.